(untitled) (Marketing Journal, 2025)
The article examines the features of the development of localization of auto components in the automotive industry of Uzbekistan in the context of modern industrial policy and technological transformations. A comparative analysis of the experience of three countries with different approaches to promoting localization is carried out — Turkey (cooperative), Brazil (state -supported), and South Korea (export - innova tive). The instruments of state support, problems of integrating local suppliers into the value chain, the role of joint ventures, and issues of financing localization projects are considered. The main problems of auto component localization in Uzbekistan are identified, including limited opportunities for cooperation, weak development of secondary suppliers, and dependence on imports of high -tech components. The article provides recommendations for the formation of a sustainable localization model based on international experience, adapted to the economic and institutional conditions of Uzbekistan.